2018
DOI: 10.3390/ijms19040994
|View full text |Cite
|
Sign up to set email alerts
|

Co-Culture with Human Osteoblasts and Exposure to Extremely Low Frequency Pulsed Electromagnetic Fields Improve Osteogenic Differentiation of Human Adipose-Derived Mesenchymal Stem Cells

Abstract: Human adipose-derived mesenchymal stem cells (Ad-MSCs) have been proposed as suitable option for cell-based therapies to support bone regeneration. In the bone environment, Ad-MSCs will receive stimuli from resident cells that may favor their osteogenic differentiation. There is recent evidence that this process can be further improved by extremely low frequency pulsed electromagnetic fields (ELF-PEMFs). Thus, the project aimed at (i) investigating whether co-culture conditions of human osteoblasts (OBs) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…This is in line with our previous work, showing that the ELF-PEMF with a frequency of f = 16 Hz, which most effectively induced osteoblast function, did not affect osteoclast function [32]. Applying the same ELF-PEMF with an only 10 Hz higher frequency, however, resulted in an increased osteoclast function [75].…”
Section: Elf-pemf Effects On Bone Cell Functionsupporting
confidence: 92%
“…This is in line with our previous work, showing that the ELF-PEMF with a frequency of f = 16 Hz, which most effectively induced osteoblast function, did not affect osteoclast function [32]. Applying the same ELF-PEMF with an only 10 Hz higher frequency, however, resulted in an increased osteoclast function [75].…”
Section: Elf-pemf Effects On Bone Cell Functionsupporting
confidence: 92%
“…The MSC-EC interaction may have a profound effect on proliferation, differentiation, cell fate and consequent angiogenesis and osteogenesis [6]. Direct contact of human ECs and MSCs has shown to increase the mineralization and ALP activity (an early osteogenic marker) both in vitro and in vivo [32][33][34][35]. In addition, Sun et al reported that MSC-EC co-culture improved bone formation and blood perfusion of the transplanted constructs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although differences exist in cell models, outcomes, endpoints, and modality of PEMF stimulation, there is robust evidence in the literature that indicates that PEMFs exert deep biological effects on osteoblastic cells and affect their proliferation and differentiation, often synergistically acting with osteogenic cues, stimulating several pathways that are known to control cell function and fate. PEMFs have been successfully tested with numerous in vitro models of osteoblastic phenotype, most noticeably rat calvaria osteoblasts [Bodamyali et al, ; Li et al, ; Kuan‐Jung Li et al, ; Selvamurugan et al, ; Hopper et al, ; Zhang et al, ; Zhou et al, ; Yan et al, ; Xie et al, ; Wang et al, ] and human bone marrow stromal cells [Sun et al, , ; Tsai et al, ; Jansen et al, ; Esposito et al, ; Ceccarelli et al, ; Fu et al, ; Kaivosoja et al, ; Petecchia et al, ; Selvamurugan et al, ; He et al, ] although primary human osteoblasts from other sources, for example, femur [Barnaba et al, ; Ehnert et al, , , ] are also well accounted for in the literature. A considerable amount of evidence has also been collected using osteoblastic cell lines, both of human origin, for example, SaOS‐2 [Hannay et al, ; Martino et al, ; Borsje et al, ; Kaivosoja et al, ] or MG‐63 [De Mattei et al, , ; Lohmann et al, ; Sollazzo et al, ; Noriega‐Luna et al, ], or of murine origin, for example, MC3T3 [Diniz et al, , ; Patterson et al, ; Sakai et al, ; Soda et al, ; Li et al, ; Lin et al, ; Zhai et al, ; Tong et al, ] or MLO‐Y4 [Lohmann et al, ; Wang et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…ALP activity significantly increased after 7 and 10 days. Ehnert et al [] observed an increase in cell proliferation by resazurin assay and differentiation by ALP activity, and Alizarin and Von Kossa staining in primary osteoblasts/adipose tissue‐derived MSC co‐cultures, using PRF bursts of 16 or 26 Hz pulses.…”
Section: Effects Of Pemfs On Osteoblastsmentioning
confidence: 99%